Kinetic evidence suggesting two mechanisms for iodothyronine 5'-deiodination in rat cerebral cortex. - Visser, T J (1982)
Enzymatic 5'-deiodination of 3,3',5'-triiodothyronine (rT3) and 3,3',5,5'-tetraiodothyronine (thyroxine, T4) was studied in microsomal preparations of rat cerebral cortex. Evidence was obtained for the existence of two thiol-dependent 5'-deiodinase entities. One of these predominates in tissue from euthyroid and long-term hypothyroid rats, is specific for rT3, follows "ping-pong" kinetics with dithiothreitol as the cosubstrate, and is inhibited by propylthiouracil (PrSUra) and iodoacetate. Inhibition by PrSUra is uncompetitive with rT3 and competitive with dithiothreitol. These properties are shared with the 5'-deiodinase activity of liver and kidney. The activity of a second type of 5'-deiodinase is highest in cerebral cortex from short-term hypothyroid rats, prefers T4 to rT3 as the substrate, is insensitive to PrSUra and iodoacetate, and follows "sequential" reaction kinetics. A similar PrSUra-insensitive 5'-deiodinase activity is also found in pituitary but is not detectable in liver and kidney; it seems, therefore, characteristic of tissues in which local T4 to 3,3',5-triiodothyronine (T3) conversion supplies a major portion of the total intracellular T3.